Innovative Design and Analysis of a Cylindrical Dielectric Resonator Antenna for High Bandwidth Applications in Sub-6GHz and Millimeter-Wave Bands - Surendra, Loya; Khan, Habibulla (Research Highlights in Science and Technology Vol. 3, 2023)
The article describes the design and simulation of a cylindrical dielectric resonator antenna (CDRA) for 5G communications with a frequency range of 2-6 GHz. The CDRA is made of alumina ceramic with a permittivity of DRA=9.9 and a resonant frequency of fr=4GHz. The antenna is excited by a microstrip line and is coupled electromagnetically to the substrate, which is Rogers RT 5880 with \(ε\)r=2.2 and tan\(δ\)=0.0009, and a thickness of 1.52mm. The CDRA operates in hybrid HEM11\(δ\) mode and has a radius of 10mm and a height of 10mm. The ground plane below the substrate is made of annealed alumina to minimize radiation below the substrate, and all radiation is directed towards the top of the CDRA. The article suggests that the designed CDRA can be used for 5G applications and massive MIMO antenna array configurations. The channel capacity of the antenna can achieve a high data rate given by the formula C=B log2(1+SNR), where C is the channel capacity and B is the bandwidth of the channel.